Pre‐operative testing for SARS‐CoV‐2 and outcomes in otolaryngology surgery during the pandemic: A multi‐center experience. Issue 4 (5th July 2021) - Kavanagh, Fergal G.; Callanan, Deirdre; Connolly, Carmel; Brinkman, David; Fitzgerald, Conall; Elsafty, Naisrin; Thong, Gerard; Hintze, Justin; Barry, Conor; Kinsella, John; Timon, Conrad; Lennon, Paul; et al.
Abstract: Introduction: Preoperative testing for COVID‐19 has become widely established to avoid inadvertent surgery on patients with COVID‐19 and prevent hospital outbreaks. Methods: A prospective cross sectional study was carried out in two university hospitals examining the pre‐operative protocols for patients undergoing otolaryngology surgery and the incidence of COVID‐19 within 30 days of surgery in patients and the otolaryngologists performing surgery. Results: One hundred and seventy‐three patients were recruited. One hundred and twenty‐three (71%) patients "cocooned" for 14 days prior to surgery. All completed a questionnaire prior to admission. One hundred and fifty‐six patients (90%) had reverse transcriptase‐polymerase chain reaction (RT‐PCR) nasopharyngeal swabs, 14 patients (8%) had CT thorax. No cases of COVID‐19 were detected among patients followed up at 30 days. Two surgeons developed COVID‐19 early during the study period. Conclusion: Current pre‐operative testing protocols consisting primarily of questionnaires and RT‐PCR resulted in zero cases of COVID in this cohort. It is possible that COVID‐19 restrictions and high proportion of patients cocooning preoperatively were factors in ensuring a low rate of COVID‐19 post‐operatively.